Bringing leadership to life in health: LEADS in a caring environment : a new perspective - Dickson, Graham; Tholl, Bill (Springer London, 2014)
Like other international jurisdictions, the Canadian health sector faces significant demands for change and improvement to meet the needs of the 21st Century.  To achieve that goal, highly sophisticated and capable leaders are required across all dimensions of the health system. Bringing Leadership to Life in Health: LEADS in a Caring Environment examines the essence of leadership itself and what it means to be a leader in today's world. The authors describe key challenges that demand reform in the health sector, examine why better leadership is the source code for better system performance, and look at the issues that stand in the way of getting that leadership.   This book describes the five domains of the Caring Environment capabilities framework: Lead Self, Engage Others, Achieve Results, Develop Coalitions, and Systems Transformation. Bringing Leadership to Life in Health: LEADS in a Caring Environment is a simple, easily accessible, and research informed book which will explain the LEADS in a Caring Environment capabilities framework that has been adopted across Canada as the foundation for health leadership talent management. This book will illustrate this framework through supportive research,  relevant stories solicited from health leaders at all levels as well as the inclusion of 'learning moments' to help the readers reflect on their own experiences.